Fluoride-mediated dephosphonylation of alpha-diazo-beta-carbonyl phosphonates - Phatake, Ravindra S.; Mullapudi, Venkannababu; Wakchaure, Vivek C.; Ramana, Chepuri V. (Organic Letters, 2017)
The possibility of fluoride-mediated selective dephosphonylation of alpha-diazo-beta-carbonyl phosphonates such as the Ohira-Bestmann reagent has been proposed and executed. The resulting alpha-diazocarbonyl intermediates undergo a (3 + 2)pcycloaddition at room temperature with conjugated olefins and benzynes. Interestingly, under the current conditions, the resulting cycloaddition products underwent either N-acylation (with excess alpha-diazo-beta-carbonyl phosphonates) or Michael addition (with conjugated olefins).

Mechano-responsive room temperature luminescence variations of boron conjugated pyrene in air - Wakchaure, Vivek C.; Ranjeesh, Kayaramkodath C.; Goudappagouda; Das, Tamal; Vanka, Kumar; Gonnade, Rajesh; Babu, Sukumaran S. (Chemical Communications, 2018)
Stimuli responsive tunable luminescence is a promising field of research. Even though mechanofluorescence is widely studied, mechanophosphorescence remains unexplored. Here we report the mechano-driven fluorescence and phosphorescence variations of a pyrene tetraboronic ester derivative. The fluorochromic and room temperature phosphorescence features are supported by theoretical studies and single crystal analysis. The mechanically ground fluorescence active but phosphorescence inactive pyrene tetraboronic ester exhibits room temperature phosphorescence in air withmechanical force. The efficient intermolecular electronic coupling in the dimer formed upon scratching enables a good communication between singlet and triplet states, hence resulting in room temperature mechanophosphorescence.

Hexaaminobenzene derived two-dimensional polymer supercapacitor with high specific capacitance and energy density - Wakchaure, Vivek C.; Kottaichamy, Alagar R.; Nidhankar, Aakash D.; Ranjeesh, Kayaramkodath C.; Nazrulla, Mohammed A.; Thotiyl, Musthafa O.; Babu, Sukumaran S. (ACS Applied Energy Materials, 2020)
Recent research interest has been shifted toward energy storage devices, especially supercapacitors, which provide high specific power and long cycle life. In this context, two-dimensional organic polymers are a class of versatile materials found to be useful in energy storage applications. However, the performance is not promising due to the low capacitance, energy density, and cyclic stability. Here, we report a two-dimensional polymer derived from hexaaminobenzene and pyromellitic dianhydride and its excellent supercapacitor performance. The specific capacitance of the two-dimensional polymer is found to be 805 F g(-1) at 0.5 A g(-1) current density in galvanostatic charge-discharge, which is the highest among the organic twodimensional polymer and most of the carbon-based materials. The superior performance of the 2D-polymer compared to a model derivative (350 F g(-1) at 0.5 A g(-1) current density) points to the critical role of a 2D-platform to excel. The high energy density, excellent cyclic stability, and low self-discharge rate support the 2D-polymer supercapacitor as a promising candidate for futuristic applications.
Keywords: 2D-polymer; energy density; Energy storage; hexaaminobenzene; supercapacitor

Efficient metal-free organic room temperature phosphors - Nidhankar, Aakash D.; Goudappagouda; Wakchaure, Vivek C.; Babu, Sukumaran Santhosh (Chemical Science, 2021)
An innovative transformation of organic luminescent materials in recent years has realised the exciting research area of ultralong room-temperature phosphorescence. Here the credit for the advancements goes to the rational design of new organic phosphors. The continuous effort in the area has yielded wide varieties of metal-free organic systems capable of extending the lifetime to several seconds under ambient conditions with high quantum yield and attractive afterglow properties. The various strategies adopted in the past decade to manipulate the fate of triplet excitons suggest a bright future for this class of materials. To analyze the underlying processes in detail, we have chosen high performing organic triplet emitters that utilized the best possible ways to achieve a lifetime above one second along with impressive quantum yield and afterglow properties. Such a case study describing different classes of metal-free organic phosphors and strategies adopted for the efficient management of triplet excitons will stimulate the development of better candidates for futuristic applications. This Perspective discusses the phosphorescence features of single- and multi-component crystalline assemblies, host-guest assemblies, polymers, and polymer-based systems under various classes of molecules. The various applications of the organic phosphors, along with future perspectives, are also highlighted.